The fall of the Constitution’s political insurance: How the Morales regime eliminated the insurance of the 2009 Bolivian Constitution - Verdugo, Sergio (Oxford Academic, 2020)
Some scholars argue that constitutions may include an insurance that aims to protect the political rights of prospective electoral losers and prevents a dominant ruling coalition from undermining the competitiveness of the political system. Although some insurance scholars have recently paid more attention to the conditions that make an insurance more likely to be effective, the scholarship seeking to identify the limits of the insurance is still scarce. The literature on courts and democratization may help us to understand those limits by exploring successful and failed experiences. In this article, I argue that after constitution-makers agree to including an insurance, the incumbent regime may delay its implementation or, if the insurance is implemented, the regime may employ different political and legal strategies to eliminate it. I identify some of these strategies using examples from the Bolivian constitutional system. I argue that the Bolivian 2009 Constitution included an insurance and that the Evo Morales regime eliminated it with the help of the Constitutional Court. Although insurance theory expects constitutional courts to guarantee key institutional arrangements, the Bolivian experience shows that constitutional courts may in fact execute the opposite task, and that after constitution makers negotiate and approve an insurance, the challenge is to secure its implementation and survival.
Keywords: 56 Ciencias Jurídicas y Derecho::5605 Derecho y legislación nacionales; ODS 16 - Paz, justicia e instituciones sólidas